İngiliz Arşiv Belgelerine Göre Cidde Anlaşması’nın İmzalanma Sürecinde İbn-i Suud-İngiliz Görüşmeleri - Mustafa BOSTANCI (Gazi Akademik Bakış)
Abdulaziz Ibn Saud, the founder of the State of Saudi Arabia, cooperated with the British to increase his power in the Arabian Peninsula and signed a special agreement with Britain on December 26, 1915. According to the treaty, the administration of the places Abdulaziz acquired would be at his disposal, and the administration would pass to his sons after him. But the rulers of these lands would in no way stand against England. After the First World War ended with the defeat of the Ottoman Empire, the forces of Ibn Saud also captured Hail, Taif, Mecca, Medina and Jeddah after 1921. Abdulaziz Ibn Saud was declared the king of Najd and Hejaz on December 5, 1924, and the “Kingdom of Najd and Hejaz” gained the status of an independent state with the Jeddah Agreement signed with Britain on May 20, 1927. In 1932, the name of the state was changed to “Kingdom of Saudi Arabia”. The Jeddah Agreement, which was signed with Britain during the independence process of the state and was an amendment to the 1915 Agreement, is very important. With the Jeddah Treaty, the absolute and definite independence of the Hijaz, Najd and its affiliates was recognized and the issue of facilitating the pilgrimage to British citizens and Muslims under British protection was approved. On the other hand, Ibn Saud promised to have friendly and peaceful relations with the sheikhs under British protection. In this research, the negotiations between England and Ibn Saud in the process leading to the signing of the Jeddah Agreement will be tried to be clarified and evaluated according to the British archival documents.